A hydrogel film and a preparation method and application thereof
By combining an interpenetrating copolymer network and a refractive index gradient transition layer, the contradiction between high peel strength and high light transmittance of the hydrogel film is resolved, achieving a balance between high adhesion and high transparency. It also has excellent self-healing ability, solving the edge warping and indentation problems of curved screens.
Patent Information
- Application Number
- CN202611042154.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-08-25
AI Technical Summary
Existing hydrogel films suffer from problems such as decreased light transmittance and increased haze when peel strength is improved, easy edge warping, and easy formation of 'orange peel' marks or deep pits when the adhesive layer is pressed. It is difficult to achieve both high peel adhesion and high light transmittance and low haze optical performance.
An interpenetrating copolymer network structure adhesive layer is adopted, which is formed by cross-linking and curing linear polymers with hyperbranched or star-shaped polymers to form an interpenetrating copolymer network. Combined with a refractive index gradient transition layer and UV gradient curing technology, the initial tack and self-healing ability of the adhesive layer are improved.
It achieves high peel strength (>1000gf/25mm), solves the problem of edge rebound and warping of curved screens, and quickly repairs indentations under pressure, maintaining high light transmittance and low haze.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic device protective materials technology, and in particular to a hydrogel membrane, its preparation method and application. Background Technology
[0002] With the rapid development of smartphone display technology, curved screens and large-curve waterfall screens have become the mainstream configuration for high-end flagship phones. To protect the display cover glass from scratches and cracks, hydrogel films, due to their excellent flexibility and adhesion, have become the preferred solution for curved screen protective films. However, clients' requirements for the fidelity of the glass screen display effect are becoming increasingly stringent (requiring high light transmittance), while the large curvature of the screen poses a serious challenge to the adhesion stability of the protective film at the edges (requiring high peel strength).
[0003] Currently, the mainstream hydrogel membrane technologies on the market mainly include: acrylic pressure-sensitive adhesive systems (using linear acrylic copolymers as the main adhesive layer) and single thermoplastic polyurethane elastomer (TPU) substrate structures (using TPU as the supporting substrate, with the adhesive layer directly coated on the substrate surface). Existing technologies have the following significant drawbacks in practical applications: In existing technologies, improving peel strength (adhesion) usually requires increasing the coating thickness of the adhesive layer or introducing a large amount of tackifying resin (such as rosin resin or petroleum resin). However, the thickness of the adhesive layer leads to increased light absorption and scattering; while tackifying resins often have a slightly yellowish phase and very limited compatibility with the host resin, which easily causes phase separation at the microscopic level, resulting in increased haze and difficulty in achieving a light transmittance of over 94%, thus failing to meet the visual requirements of ultra-high-definition displays.
[0004] For curved glass, the edges of the hydrogel film will be subjected to rebound stress after lamination. The peel strength of existing hydrogel film adhesives is mostly in the range of 20-100gf / 25mm. After long-term use, problems such as bubbles, edge lifting or warping are very likely to occur at the edges.
[0005] Most of the hydrogel film adhesive layers on the market have a linear molecular structure. When subjected to external pressure, the molecular chains inside the adhesive layer are prone to irreversible displacement, which can easily produce visible "orange peel" marks or deep pits. Summary of the Invention
[0006] This invention provides a hydrogel film, its preparation method, and its application, to solve the defects of existing hydrogel films for curved screens, such as decreased light transmittance and increased haze when the peel force is increased (a physical antagonistic contradiction between high adhesion and high transparency), easy edge warping, and easy formation of "orange peel" marks or deep pits under pressure. The invention achieves a hydrogel film that combines high peel adhesion and high light transmittance with low haze optical performance, and optimizes the cohesive performance and self-healing ability of the adhesive layer under pressure.
[0007] In a first aspect, the present invention provides a hydrogel membrane comprising a substrate layer and a structural adhesive layer; The structural adhesive layer includes an interpenetrating copolymer network, which includes an interpenetrating first three-dimensional cross-linked network and a second three-dimensional cross-linked network. The first three-dimensional cross-linked network is formed by intermolecular cross-linking and curing of a first polymer, and the second three-dimensional cross-linked network is formed by intermolecular cross-linking and curing of a second polymer. The first polymer comprises a linear polymer, the linear polymer comprising a first polymerizable functional group; The second polymer includes hyperbranched polymers and / or star polymers, wherein the ends of the hyperbranched polymers and / or star polymers include second polymerizable functional groups complementary to the first polymerizable functional group; The first three-dimensional cross-linked network and the second three-dimensional cross-linked network are connected by covalent bonds through the interaction of the first polymerizable functional group and the second polymerizable functional group.
[0008] A second aspect of the present invention provides a method for preparing a hydrogel membrane as described in the first aspect, comprising: depositing a structural adhesive slurry comprising the first polymer and the second polymer onto the substrate layer, and obtaining the hydrogel membrane by a curing reaction.
[0009] A third aspect of the present invention provides an application of the hydrogel membrane as described in the first aspect in the protection of electronic devices.
[0010] Compared with the prior art, the beneficial effects of the present invention are as follows: The hydrogel membrane of this invention has a structural adhesive layer formed by the cross-linking and curing of a first polymer and a second polymer in the substrate layer. Unlike the limited cross-linking of traditional linear molecules, this structural adhesive layer is an interpenetrating copolymer network formed by the cross-linking and curing of linear polymers with hyperbranched or star-shaped polymers. The first polymer provides the first backbone network of the structural adhesive layer, forming a flexible and scalable linear backbone, facilitating interpenetration with the second polymer during the curing process and supporting the subsequent embedding of the second polymer as cross-linking nodes. The second polymer achieves interpenetration through end-group cross-linking and embedding, while simultaneously forming strong interactions through covalent cross-linking, thereby enhancing the initial tack and overall cohesion of the adhesive layer. The formation of a dense chemical cross-linking network enables the peel force to stably exceed 1000gf / 25mm, which is nearly 100% higher than that of traditional hydrogel films. In addition, this hydrogel film completely solves the problem of edge rebound and warping of curved screens. The interpenetrating first and second three-dimensional cross-linking networks formed by the structural adhesive layer have significant elastic recovery energy. When subjected to external pressure and indentation, it can quickly generate recovery stress. Combined with the local fluidity of hyperbranched molecules or star polymers, the indentation can be repaired without leaving a mark within 30 seconds. This improves the cohesive defects and indentation repair force of the high-viscosity adhesive layer of the hydrogel film, and solves the defects of easy glue overflow and "orange peel" marks after pressure. Detailed Implementation
[0011] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0012] Unless otherwise specified, specific techniques or conditions in the embodiments of this invention shall be performed in accordance with the techniques or conditions described in the literature in this field, or in accordance with the product instructions. Devices, instruments, reagents, etc., whose manufacturers are not specified are all conventional products that can be purchased through legitimate channels. All raw materials used in this invention are readily available in the domestic market.
[0013] In this invention, the technical features described in an open-ended manner include both closed-ended technical solutions composed of the listed features and open-ended technical solutions that include the listed features.
[0014] In this invention, numerical ranges are involved. Unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included.
[0015] hydrogel membrane In a first aspect, the present invention provides a hydrogel membrane comprising a substrate layer and a structural adhesive layer; The structural adhesive layer includes an interpenetrating copolymer network, which includes an interpenetrating first three-dimensional cross-linked network and a second three-dimensional cross-linked network. The first three-dimensional cross-linked network is formed by intermolecular cross-linking and curing of a first polymer, and the second three-dimensional cross-linked network is formed by intermolecular cross-linking and curing of a second polymer. The first polymer comprises a linear polymer, the linear polymer comprising a first polymerizable functional group; The second polymer includes hyperbranched polymers and / or star polymers, wherein the ends of the hyperbranched polymers and / or star polymers include second polymerizable functional groups complementary to the first polymerizable functional group; The first three-dimensional cross-linked network and the second three-dimensional cross-linked network are connected by covalent bonds through the interaction of the first polymerizable functional group and the second polymerizable functional group.
[0016] As should be known to those skilled in the art, both the first polymer and the second polymer are prepolymers.
[0017] Interpenetrating polymer network (IPN): An IPN is composed of two or more polymers that are interwoven and interpenetrated at the molecular level. The interpenetrating copolymer network of the present invention is obtained by derivatization and modification of the IPN structure. In this invention, not only are each polymer network (the first three-dimensional cross-linked network and the second three-dimensional cross-linked network) connected internally by chemical cross-linking bonds, but the two networks are also chemically bonded to each other through the reaction between the second polymerizable functional group at the end of the second polymer and the first polymerizable functional group of the first polymer, thereby forming a stable network with both high cross-linking density and excellent interpenetrating structure.
[0018] The role of the specific structural adhesive layer in the hydrogel membrane of this invention: (1) Improve adhesion and cohesive strength of the adhesive layer: Hyperbranched polymers and / or star polymers with second polymerizable functional groups at the ends form a highly cross-linked interpenetrating copolymer network with linear polymers containing first polymerizable functional groups, providing high peel strength; at the same time, the integrity of the network structure enhances the cohesive strength of the adhesive layer, preventing the problem of adhesive overflow that is prone to occur under high adhesion. (2) Enhanced self-healing ability: The interpenetrating copolymer network endows the colloid with good elastic recovery properties. When subjected to external pressure, the flexible segments in the network can slide and deform to absorb stress. After the external force is removed, the elastic force provided by the crosslinking nodes drives the structure to reset, thereby achieving rapid repair of the indentation; (3) It can significantly improve crosslinking density and cohesive strength without significantly increasing brittleness and damaging optical properties, thus solving the industry problem of traditional hydrogel films being unable to balance optical performance and mechanical adhesion performance.
[0019] In addition, the second polymer (hyperbranched polymer or star polymer) plays a key role as a "multifunctional crosslinking hub" and "network enhancer" in the structural adhesive layer. Its main functions are as follows: a) It provides high-density crosslinking points. Its high functionality allows each hyperbranched polymer or star polymer molecule to react with linear polymers and other hyperbranched polymers or star polymer molecules through its terminal second polymerizable functional group during UV curing, forming a dense chemical crosslinking network; b) It constructs an interpenetrating structure with the first polymer. The interpenetrating structure can effectively dissipate stress and endow the adhesive layer with high toughness and creep resistance; c) The hyperbranched or star structure allows it to maintain a low viscosity even at high viscosity, which is beneficial for precise coating and can prevent the sedimentation of nanoparticles in the system, maintaining the stability of the system.
[0020] In some specific embodiments, the mass ratio of the first polymer to the second polymer is (40~70):(8~24).
[0021] In some specific embodiments, the number of the second polymerizable functional groups is ≥16; the second polymerizable functional group is selected from at least one of acrylate group, vinyl ether group, and allyl ether group, preferably acrylate group.
[0022] In some preferred embodiments, the hyperbranched polymer is selected from at least one of hyperbranched polyester, hyperbranched polyether, and hyperbranched polyamide; the star-shaped polymer is selected from at least one of star-shaped polyacrylate and star-shaped polystyrene. In some preferred embodiments, the second polymer is selected from hyperbranched polyurethane acrylate (HPUA).
[0023] The inventors have discovered that the spherical structure (spherical molecular morphology) of HPUA and its numerous active end groups (at least 16 active reaction sites) can form a highly cross-linked IPN with linear acrylates. Introducing HPUA with its highly branched spherical structure into a hydrogel pressure-sensitive adhesive system, instead of a traditional linear tackifying resin, provides a peel strength of >1000gf while maintaining transparency, breaking the industry's myth that increased tack inevitably leads to decreased transparency. The spherical structure and numerous active end groups of HPUA can form a highly cross-linked interpenetrating copolymer structure with the first polymer, providing high peel strength. Simultaneously, the overall integrity of the network structure enhances the cohesive strength of the adhesive, preventing the overflow problem that easily occurs under high viscosity.
[0024] Hyperbranched polyurethane acrylates possess advantages such as high-density anchor points, high-functionality crosslinking, and improved rheological properties. Their molecular morphology is a highly branched spherical shape with several acrylate functional groups at the ends, totaling ≥16 terminal functional points. As a high-functional component with hyperbranched crosslinking points, it exhibits low bulk viscosity and high-functionality parallel crosslinking capability. Its function is to provide a second "node network" in interpenetrating copolymerization. Through a large number of terminal bifunctional or multifunctional acrylate groups, it forms a dense network crosslinking with linear polymers, significantly improving the peel strength of the adhesive layer (>1000gf / 25mm target value). Furthermore, it enhances the mechanical strength, temperature resistance, and self-healing properties of the adhesive layer, resulting in superior performance in curved surface bonding and indentation repair.
[0025] In some specific embodiments, the linear polymer is a linear acrylate polymer; preferably, the linear acrylate polymer is selected from a homopolymer of one of isooctyl acrylate, isobornyl acrylate, and hydroxyethyl acrylate, or a copolymer of at least two of them. More preferably, the linear polymer is selected from acrylate copolymers.
[0026] In some specific embodiments, the molecular weight (number average molecular weight) of the linear acrylate polymer is 50,000 to 80,000. The linear acrylate polymer includes, but is not limited to, linear methacrylate copolymers, epoxy acrylates, polyester acrylates, ketone acrylates, etc.; for example, it may be a copolymer of methyl methacrylate (MMA) and the flexible monomer butyl acrylate.
[0027] The linear acrylate polymers in this scheme have a molecular weight of 50,000 to 80,000, forming a flexible linear backbone with good rheological properties and coatability. The first polymer provides the first backbone network of the structural adhesive layer, forming a flexible and scalable linear main chain that supports the subsequent embedding of the second polymer as a crosslinking node. The first polymer retains sufficient hydroxyl / carboxyl functional groups to facilitate the end-group crosslinking and embedding of the second polymer, achieving interpenetration through covalent or strong interactions, thereby improving the initial tack and overall cohesion of the structural adhesive layer.
[0028] In some specific embodiments, preferably, the linear acrylate polymer is a linear acrylate copolymer because it best balances high light transmittance, suitable glass transition temperature Tg, moderate modulus, abundant free radical reaction sites, and compatibility with hyperbranched or star polymers, which other systems cannot fully achieve.
[0029] In some specific embodiments, preferably, the linear acrylate polymer is selected from homopolymers of one or more of isooctyl acrylate (2-EHA), isobornyl acrylate (IBOA), and hydroxyethyl acrylate (HEA), or copolymers of at least two of them. The linear acrylate polymer in this solution is selected from the above polymers, possessing the beneficial effects of high molecular weight and good linear backbone flexibility. The molecular weight range is typically in the tens of thousands or even higher, providing good rheological properties and coatability. Furthermore, it provides the first "backbone" network of the IPN, forming a flexible and scalable linear backbone to support the subsequent embedding of hyperbranched polymers or star polymers as crosslinking nodes. The linear acrylate polymer retains sufficient hydroxyl / carboxyl functional groups, facilitating the end-group crosslinking and embedding of hyperbranched polymers or star polymers, achieving interpenetration through covalent or strong interactions, thereby improving the initial tack and overall cohesiveness of the adhesive layer.
[0030] In some specific embodiments, the thickness of the structural adhesive layer is ≥25μm. This solution controls the thickness of the structural adhesive layer to be ≥25μm. 25μm is the lower limit of thickness because it is the minimum thickness required to achieve high-density crosslinking and IPN network formation, which is sufficient to ensure adhesion and structural strength.
[0031] In some preferred embodiments, the thickness of the structural adhesive layer is 25~50μm. This solution controls the thickness of the structural adhesive layer to 25~50μm, with 50μm as the upper limit, because exceeding this value would significantly increase the overall module thickness, affecting the product's slim design. Similarly, an excessively thick adhesive layer would introduce greater internal stress, increasing coating costs.
[0032] Traditional hydrogel films typically consist of a multi-layer interface formed by a TPU substrate and a pressure-sensitive adhesive layer. The refractive index of TPU is generally between 1.48 and 1.50, while the refractive index of commonly used pressure-sensitive adhesives is generally between 1.45 and 1.47, and the refractive index of conventional mobile phone optical glass is between 1.51 and 1.52. Due to the significant refractive index jumps between the layers, light undergoes multiple Fresnel reflections at the interface. This not only directly reduces the overall light transmittance but also causes screen reflections and ghosting.
[0033] Refractive index (RI): The ratio of the speed of light in a vacuum to its speed of light in a medium, is an important parameter characterizing the optical properties of a material. In the use of display cover glass, light needs to pass through air, the protective film substrate, the protective film adhesive layer, and the phone cover glass. This means there are multiple interfaces: air-substrate, substrate-adhesive layer, and adhesive layer-phone cover glass. If the refractive index difference at each interface is large, it will cause significant light reflection at each interface, which will accumulate and lead to a substantial decrease in overall light transmittance.
[0034] In some specific embodiments, the refractive index difference between the substrate layer and the structural adhesive layer is ≤0.01. This solution controls the refractive index difference between the substrate layer and the structural adhesive layer to be ≤0.01, which minimizes light reflection loss and ensures that most light is transmitted to the mobile phone screen. This reduces Fresnel reflection loss at the interfaces between layers, achieving high transmittance.
[0035] In some specific embodiments, the hydrogel film further includes a refractive index gradient transition layer, which is located between the substrate layer and the structural adhesive layer; The refractive index of the substrate layer is denoted as n1; The refractive index of the refractive index gradient transition layer is denoted as n2; The refractive index of the structural adhesive layer is denoted as n3; The n1, n2, and n3 satisfy the condition: n1 < n2 < n3.
[0036] This solution does not limit the type of matrix resin raw material for the refractive index gradient transition layer. For example, low viscosity and easy UV curing of acrylate monomers or oligomers can be selected as the matrix resin raw material for constructing the transition layer. For example, the monomers are butyl acrylate (BA), ethyl acrylate (EA), isooctyl acrylate (IOA), etc.; the oligomers are oligomers of polyacrylate or acrylate copolymers with a molecular weight of several thousand to ten thousand.
[0037] The refractive index gradient transition layer located between the substrate layer and the structural adhesive layer in this solution primarily functions to smooth the refractive index jump between the substrate layer and the structural adhesive layer using the refractive index measured by an ellipsometer. This significantly reduces the refractive index difference between the interfaces, effectively suppresses Fresnel reflection, achieves high refractive transmittance, and improves the color reproduction of the glass cover display.
[0038] This solution adds a refractive index gradient transition layer between the substrate layer and the structural adhesive layer. This technique makes the refractive index of the overall structure change in a gradient, effectively suppressing coherent scattering and reflection loss at the interface, improving the total light transmittance of the hydrogel film and reducing haze, resulting in a near-invisible effect to the naked eye.
[0039] In some preferred embodiments, the thickness of the refractive index gradient transition layer is 50~200 nm. The thickness of the refractive index gradient transition layer in this solution falls within this range. Can avoid The refractive index change is too steep, effectively reducing interface reflection without introducing additional absorption and scattering, ensuring overall light transmittance, and without increasing internal stress, thus avoiding affecting the film's flexibility. Precision coating technologies such as micro-grooving and slot extrusion are controllable and feasible in the 50~200nm range.
[0040] In some specific embodiments, the structural adhesive layer comprises a refractive index modifier modified with a silane coupling agent; and / or, the refractive index gradient transition layer comprises a refractive index modifier modified with a silane coupling agent; The refractive index modifier, without modification by the silane coupling agent, is selected from at least one of nano-sized ZrO2, TiO2, Ta2O5, Nb2O5, and HfO2, preferably nano-sized ZrO2. The silane coupling agent can be any conventional silane coupling agent used in the art to improve the interfacial compatibility between inorganic materials and resins, without special limitations; it can be selected from at least one of functionalized silane coupling agents such as amino, epoxy, vinyl, methacryloxy, mercapto, and acetoxy. For example, it can be KH-560, KH-570, KH-550, KH-569, KH-575, and KH-590, but is not limited to the listed silane coupling agents; other unlisted silane coupling agents are also applicable.
[0041] The refractive index gradient transition layer and structural adhesive layer in this design both include refractive index modifiers and silane coupling agents. On one hand, dispersing the refractive index modifier in nano-form within the resin effectively increases the refractive index of both the structural adhesive layer and the refractive index gradient transition layer, facilitating optical matching with the mobile phone glass cover. Simultaneously, the rigid support of the inorganic particles in the refractive index modifier enhances the puncture resistance of the hydrogel film. On the other hand, the silane coupling agent-modified refractive index modifier can chemically bond or strongly interact with the resin (especially through chemical bonding between the silane coupling agent and the end groups of hyperbranched or star-shaped polymers), improving the uniformity and stability of dispersion and preventing light scattering and refractive index unevenness caused by particle agglomeration. It also improves adhesion; this transition layer enhances the chemical bonding between the structural adhesive layer and the substrate layer.
[0042] The refractive index modifier modified with silane coupling agent of this invention refers to the chemical bonding of silane coupling agent to the surface of refractive index modifier particles.
[0043] In some specific embodiments, the mass of the refractive index modifier modified by the silane coupling agent is m1, and the mass of the low viscosity and easily UV-curable acrylate monomer or oligomer is m2, and m1:m2 = (1:45) ~ (1:4).
[0044] In some specific embodiments, the refractive index of the structural adhesive layer is maintained by a combination of high-refractive-index aromatic cyclic monomers in hyperbranched or star-shaped polymers and a refractive index modifier.
[0045] In some specific embodiments, the Dv50 of the silane coupling agent-modified refractive index modifier is ≤15nm. The refractive index modifier in this scheme has a Dv50 within this range, and its surface is modified with a silane coupling agent, resulting in good dispersion stability. It is used for optical control of structural adhesive layers and / or refractive index gradient transition layers. It has two main functions: first, it obtains a stable refractive index gradient range through the refractive index modifier, ensuring that the refractive index difference between adjacent layers is ≤0.01; second, the surface modification of the refractive index modifier with the silane coupling agent facilitates chemical anchoring and mechanical interlocking.
[0046] In this invention, Dv50 refers to the particle size at which the cumulative particle size distribution number reaches 50% in the volume cumulative distribution curve. As an example, Dv50 can be conveniently determined using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK, according to GB / T 19077-2024 Particle Size Distribution Laser Diffraction Method.
[0047] The role of the silane coupling agent in this solution also includes: establishing a chemical bridge between the organic polymer (structural adhesive layer) and the inorganic substrate (glass cover), enhancing the interfacial bonding strength, improving resistance to damp heat, and increasing durability.
[0048] In some embodiments, the hydrogel film also includes a hydrophobic and oleophobic coating to provide fingerprint resistance and a smooth feel.
[0049] In some specific embodiments, the thickness of the hydrophobic and oleophobic coating in the hydrogel film is 10~50nm, wherein the hydrophobic and oleophobic coating includes, but is not limited to, a nano-fluorosilicone coating. The thickness of the hydrophobic and oleophobic coating in this solution is within this range, which avoids uneven coating or easy wear, and also takes into account the cohesive stress of the coating and its adhesion to the underlying substrate, reducing the risk of coating peeling.
[0050] In some specific embodiments, the thickness of the substrate layer is 80~150μm. This solution controls the thickness of the substrate layer within this range. The reason for considering the lower limit of the thickness as 80μm is to maintain the rigidity of the material and prevent excessive deformation during use. The upper limit is set at 150μm, which is based on considerations such as the overall thickness, weight, cost, and feel of the hydrogel film.
[0051] In some embodiments, the hydrogel film further includes a release liner. The release liner includes, but is not limited to, a polyethylene terephthalate (PET) protective film with a surface treated with low fluorine content.
[0052] In some specific embodiments, the hydrogel membrane sequentially comprises a hydrophobic and oleophobic coating, a substrate layer, a refractive index gradient transition layer, and a structural adhesive layer.
[0053] In some specific embodiments, the hydrogel membrane sequentially comprises a hydrophobic and oleophobic coating, a substrate layer, a refractive index gradient transition layer, a structural adhesive layer, and a release protective layer.
[0054] A second aspect of the present invention provides a method for preparing a hydrogel membrane as described in the first aspect, comprising: depositing a structural adhesive slurry comprising the first polymer and the second polymer onto the substrate layer, and obtaining the hydrogel membrane by a curing reaction.
[0055] In some specific embodiments, the curing reaction includes: a pre-curing reaction that enables the hyperbranched polymer or star polymer to achieve a conversion rate of 60% to 70%; The photocuring wavelength of the pre-curing reaction is 365nm~405nm, and the photocuring power is 100mW / cm². 2 ~500mW / cm 2 .
[0056] In some specific embodiments, the curing reaction includes a pre-curing reaction and a deep curing reaction; The conditions for the pre-curing reaction include: a photocuring wavelength of 365nm~405nm and a photocuring power of 100mW / cm².2 ~500mW / cm 2 This enables hyperbranched or star-shaped polymers to achieve a conversion rate of 60% to 70%. The conditions for the deep curing reaction include: a photocuring wavelength of 365nm~405nm and a photocuring power of 800mW / cm². 2 ~1500mW / cm 2 This promotes the complete curing of hyperbranched or star-shaped polymers.
[0057] This solution provides the aforementioned UV gradient curing method, which uses ultraviolet (UV) light of different powers and wavelengths to distribute and cure the material. In this solution, a light curing wavelength of 365nm~405nm and a light curing power of 100mW / cm² are first used for curing. 2 ~500mW / cm 2 The LED pre-cured surface (enabling hyperbranched or star-shaped polymers to achieve a conversion rate of 60%~70%) is then photocured with a wavelength of 365nm~405nm and a photocuring power of 800mW / cm². 2 ~1500mW / cm 2 Deep curing (complete curing of hyperbranched or star-shaped polymers). The principle behind this UV gradient curing method is as follows: the pre-curing stage avoids excessively high instantaneous energy that could lead to rapid monomer polymerization, air bubbles, or internal stress, ensuring low haze in the cured adhesive layer; the subsequent deep curing stage fully drives the hyperbranched or star-shaped polymers to interpenetrate and crosslink with linear acrylate polymers, forming a complete interpenetrating copolymer network structure, ensuring high viscosity, high cohesion, and strong self-healing properties. In addition, compared with ordinary thermosetting, UV curing is faster, more efficient, and avoids damage to the structural adhesive layer caused by high temperatures.
[0058] This solution uses the aforementioned UV gradient curing process to replace the traditional thermosetting process, which not only increases production speed but also avoids the risks of thermal degradation and yellowing of the structural adhesive layer caused by prolonged heating. Due to the high reactivity of hyperbranched or star-shaped polymers, this solution results in extremely low monomer residue after curing, low VOC emissions, and better optical stability (it will not yellow or become tacky even after prolonged exposure to ultraviolet light).
[0059] This solution utilizes the interpenetrating copolymer network formed by UV gradient curing to achieve a macroscopically strong cohesive energy (anti-spillage adhesive) and a microscopically high free volume (rapid self-healing). This specific network crosslinking morphology enables the molecular chains to remain unslipped and prevent permanent physical deformation under high stress on 3D curved surfaces.
[0060] The formation mechanism of the interpenetrating co-convergent network in this scheme: (1) During the UV curing process, linear polymers (such as linear acrylate polymers) form a flexible long-chain backbone.
[0061] (2) Hyperbranched or star-shaped polymers rapidly interpenetrate and solidify in the long-chain backbone while forming highly cross-linked nodes with linear polymers (such as linear acrylate polymers).
[0062] (3) Technical effect: This structure exhibits extremely high peeling force (>1000gf) on a macroscopic scale because hyperbranched polymer or star polymer molecules provide great surface contact energy; on a microscopic scale, it exhibits excellent self-healing properties. When under pressure, the local non-crosslinked flexible segments can undergo molecular slippage to dissipate stress, and after the external force is removed, they are driven to reset by the elastic force of the crosslinked nodes.
[0063] In some specific embodiments, the curing reaction system further includes a tackifier / wetting agent. The tackifier / wetting agent in this solution can improve the wettability of the structural adhesive layer with the substrate layer and the glass cover, reduce surface tension, promote uniform coating, and enhance initial tack. The tackifier / wetting agent is a type of resin that can improve the wettability of the structural adhesive layer with the substrate layer and the glass cover, reduce surface tension, promote uniform coating, and enhance initial tack, and is not limited to specific components. Examples include hydrogenated rosin esters, rosin glycerol esters, pentaerythritol esters, and terpene resins, but are not limited to the listed tackifiers / wetting agents; other unlisted tackifiers / wetting agents are also applicable.
[0064] In some specific embodiments, the tackifier / wetting agent and the silane coupling agent can synergistically enhance the wetting and surface anchoring of the structural adhesive layer onto the glass cover. Simultaneously, the synergistic effect of the tackifier / wetting agent and the silane coupling agent with linear acrylate polymers and hyperbranched or star-shaped polymers increases the overall viscosity and cohesiveness of the tackifying resin, while the silane coupling agent improves intermolecular interfacial bonding, ensuring that the adhesiveness remains even at the edges under high stress.
[0065] In some specific embodiments, the initiator in the curing reaction system is one or more photoinitiators capable of initiating free radical polymerization via ultraviolet light, and its absorption spectrum matches the UV light source used. The photoinitiator includes, but is not limited to, α-hydroxy ketones, benzoylphosphine oxides, amino ketones, and their compound systems. For example, it can be photoinitiator TPO (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and photoinitiator 1173 (2-hydroxy-2-methyl-1-phenylpropanone), but is not limited to the listed photoinitiators; other unlisted photoinitiators are also applicable. The photoinitiator is used for rapid curing under ultraviolet light.
[0066] In some specific embodiments, the curing reaction system further includes a stabilizer, which is one or more light stabilizers and / or antioxidants. The light stabilizers include, but are not limited to, hindered amines, hindered phenols, and phosphite stabilizers. The stabilizer in this solution is used to inhibit yellowing and oxidative degradation after UV light initiation, extending the adhesive layer's lifespan. Its key functions are: a) Under gradient UV curing technology, the photoinitiator provides free radicals for the polymerization reaction, triggering crosslinking between linear acrylate polymers and hyperbranched or star-shaped polymers, promoting a complete IPN structure; b) The stabilizer can reduce yellowing and oxidative degradation caused by photoaging, extending the adhesive layer's lifespan and ensuring long-term light transmittance and appearance stability.
[0067] In some specific embodiments, the structural adhesive layer slurry comprises the following raw materials in parts by weight: 40-70 parts of linear acrylate polymers; 8-24 parts of hyperbranched or star-shaped polymers; 2-10 parts of refractive index modifier modified with silane coupling agent; Component D (8-20 parts of tackifier / wetting agent, 0.5-1.5 parts of silane coupling agent); used to enhance chemical anchoring to the glass surface, wherein the tackifier / wetting agent includes, but is not limited to, hydrogenated rosin glycerol ester; and the silane coupling agent includes, but is not limited to, epoxy silane coupling agent. 1-5 parts of initiator; Stabilizer 0.1~0.5 parts.
[0068] In this scheme, the silane coupling agent in the refractive index modifier modified by the silane coupling agent in the structural adhesive layer slurry can be the same as or different from the silane coupling agent in component D.
[0069] In some specific embodiments, hydrogenated rosin glycerol esters need to undergo decolorization treatment, and the decolorized hydrogenated rosin glycerol esters should meet the following indicators: (1) Colorimetric (Gardner Scale): ≤2, preferably ≤1.
[0070] (2) The transmittance at a wavelength of 425 nm (measured by dissolving in toluene at 10% by weight) is ≥90%, preferably ≥95%.
[0071] (3) Acid value (mg KOH / g) ≤5, preferably ≤3.
[0072] The decolorization process can be carried out using methods commonly used in the field or further refined using chemical methods such as hydrogenation and esterification. Using hydrogenated rosin glycerol ester that meets the above-mentioned indicators can effectively avoid the negative impact of its own color or impurities on the light transmittance and haze of the structural adhesive layer.
[0073] In some specific embodiments, the method for preparing the refractive index gradient transition layer includes the following steps: (1) Preparation of dispersion of refractive index gradient transition layer: a. Surface modification: mix nano zirconium dioxide powder with silane coupling agent in solvent, with a typical mass ratio of nano zirconium dioxide: silane coupling agent = 100: (1~5). Stirring and reacting at 60~80℃ for 2~4 hours to chemically bond the silane coupling agent to the surface of the nano-zirconia particles, resulting in a silane coupling agent modified nano-zirconia dispersion; b. Dispersion: Mix the silane coupling agent modified nano-zirconia dispersion with a low-viscosity acrylate monomer (such as isooctyl acrylate IOA) or oligomer (with the mass of the modified nano-zirconia in the modified nano-zirconia dispersion as m1, the mass of the low-viscosity acrylate monomer or oligomer as m2, m1:m2=(1:45)~(1:4), pre-disperse in a high-speed disperser for 25~40 minutes to form a primary dispersion with a solid content of 20wt%~40wt%; c. Grinding: Transfer the primary dispersion to a three-roll mill or bead mill for fine grinding for 1~2 hours to obtain a uniform and stable refractive index gradient transition layer dispersion. (2) Preparation of the refractive index gradient transition layer: A series of refractive index gradient transition layer slurries with varying concentrations (e.g., 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%) are pre-prepared from the aforementioned refractive index gradient transition layer dispersion. First, a minimum concentration of 5 wt% slurry is coated onto an optical substrate layer (e.g., a TPU film) to form a wet film. Then, while the previous coating is uncured or slightly pre-cured (UV irradiation causes initial gelation of the surface but the interior remains liquid), a 10 wt% slurry is immediately applied. Since both layers are liquid or semi-liquid, diffusion and mixing occur at the interface, naturally forming a concentration transition zone. This step is repeated, sequentially overcoating (using a gravure roller coating or slot extrusion coating machine) higher concentration slurries until the desired total thickness and final nanoparticle concentration are achieved. All overcoated layers are then UV cured.
[0074] In some specific embodiments, the method for preparing the hydrogel membrane includes the following steps: (1) The preparation method of the modified nano-zirconia dispersion is the same as the preparation method of the modified nano-zirconia dispersion in the refractive index gradient transition layer.
[0075] (2) Preparation of structural adhesive layer slurry (the core is to avoid high viscosity components such as hyperbranched polymers or star polymers being mixed with other components in large quantities too early, resulting in uneven dispersion, and to ensure that the refractive index regulator is introduced last to minimize the risk of agglomeration.): a. Preparation of main premix: Using a planetary mixer or a double planetary mixer with scraping and dispersing functions, the steps are as follows: In the mixing tank, first add linear acrylate polymers, and while stirring at low speed (100~400rpm), slowly add thickener / wetting agent (hydrogenated rosin glycerol ester) (60~180g / min), and then while stirring at low speed (100~400rpm), add stabilizer and part (accounting for 30%~70% of the mass of photoinitiator, preferably 50%) of photoinitiator (e.g., the total amount of 1173). b. Slowly add the preheated hyperbranched polymer or star-shaped polymer (60~180g / min) to the above main premix and mix for 10~20 minutes. Under continuous low-speed (100~400rpm) stirring, slowly add the pre-prepared modified nano-zirconia dispersion in a thin stream (60~180g / min). Then add the silane coupling agent in component D and the remaining photoinitiator (e.g., all of the TPO used). Mix for 15~25 minutes to ensure that the nanoparticles are uniformly dispersed in the system.
[0076] (3) Vacuum degassing (because the IPN system has high viscosity, degassing is crucial to ensure that the adhesive layer is free of defects after coating) and filtration (to remove any possible trace gel particles or impurities).
[0077] (4) Coating: Coating is performed on the surface of the substrate layer or the transition layer of the composite film of substrate layer-refractive index gradient transition layer (using a slit extrusion coating machine or a precision doctor blade coating machine, controlling the thickness specification of 25~50μm). (5) UV curing.
[0078] In some specific embodiments, the method for preparing the hydrogel membrane includes: (1) Substrate pretreatment: The TPU substrate is subjected to online corona treatment to increase the surface tension to more than 50 dyn / cm (to improve the adhesion of subsequent coatings).
[0079] (2) Refractive index gradient transition layer coating: The refractive index gradient transition layer slurry is coated onto the substrate by micro-grooving roller coating and then dried to form a nano-scale thin film.
[0080] (3) Structural adhesive layer coating: A high-precision slot-die is used to coat the adhesive onto the transition layer to ensure that the thickness tolerance is controlled within ±1μm.
[0081] (4) UV gradient curing: First stage (pre-curing): Using low power (100mW / cm²) 2 ~500mW / cm 2 The LED 395nm cold light source enables the adhesive layer to achieve a conversion rate of 60%~70%, ensuring optical transparency.
[0082] The second stage (deep curing): UV-LED light source is used for full-band irradiation to promote the complete penetration of hyperbranched molecules and achieve the final cohesive strength.
[0083] (5) Lamination and slitting: Lay the fluorine release film in a dust-free environment and cure it at room temperature.
[0084] A third aspect of the present invention provides an application of the hydrogel membrane as described in the first aspect in the protection of electronic devices; In some specific embodiments, the electronic device includes a display cover glass, an optical lens module, a flexible display module, a touch sensor, a biometric sensor cover, or an in-vehicle display panel.
[0085] The present invention is further illustrated below with specific embodiments: The specific information of each raw material used in the hydrogel membrane preparation method provided in Example 1 is as follows: Linear acrylate copolymer: DEGALAN® PM 703 from Evonik (number average molecular weight: 70,000); HPUA: CN2303 from Sartoma, HPUA has 18 terminal polymerizable functional groups; Hydrogenated rosin glycerides: Kraton's SYLVALITE TM RE 110L; Silane coupling agents: KH-560: Momentive's Silquest® A-187; Photoinitiator Irgacure 1173: Irgacure® 1173 from BASF; Photoinitiator TPO: Irgacure® TPO from BASF; Hindered amine light stabilizer (HALS): Tinuvin® 1130 from BASF; TPU film: Pearlthane® D12T85 from Lubrizol; IOA of isooctyl acrylate: Viscoat #155 from Nippon Shokubai Co., Ltd. Nano-zirconia: SZR-M from Sakai Chemical Co., Ltd., Japan.
[0086] A nano-zirconia dispersion with a solid content of 30 wt% modified by a silane coupling agent (particle size Dv) 50 The preparation method of (8nm) is as follows: I. Surface Modification Pretreatment: 1. Weigh 100 parts by weight of nano-zirconia (SZR-M) powder and place it in a high-speed dispersion vessel.
[0087] 2. Add 3 parts by weight of KH-560 and 200 parts by weight of isooctyl acrylate IOA.
[0088] 3. Stir at 500 rpm for 3 hours at 70±5℃. During this process, KH-560 hydrolyzes and undergoes a condensation reaction with the hydroxyl groups on the surface of nano-zirconia, thus achieving modification.
[0089] 4. After the reaction is complete, a preliminarily mixed slurry is obtained.
[0090] II. Fine grinding and dispersion: 1. Transfer the slurry to the grinding jar of a planetary ball mill. Add zirconia grinding beads at a volume ratio of 2:1 to the slurry.
[0091] 2. Grinding and dispersion are carried out under circulating water cooling (temperature < 40℃). The ball mill speed is set to 300 rpm.
[0092] 3. Take samples every hour and measure the particle size distribution Dv50 of the slurry using a laser particle size analyzer.
[0093] 4. When the Dv50 stabilizes at 8nm and the particle size distribution shows a narrow single-peak distribution, stop grinding.
[0094] III. Preparation and Post-processing: 1. Separate the grinding beads to obtain a concentrated nano-zirconia slurry. Dilute the concentrated slurry using additional IOA and precisely adjust it to a solid content of 30 wt%.
[0095] 2. Add 0.3wt% of dispersant BYK-111 and stir at 400rpm for 30 minutes to ensure long-term storage stability.
[0096] 3. Place the dispersion in a vacuum degassing machine and remove bubbles for 20 minutes under a vacuum of -0.095 MPa.
[0097] 4. Filter using a 400-mesh filter to complete the preparation.
[0098] Example 1 1. This embodiment provides a hydrogel membrane, which sequentially includes a substrate layer (100μm), a refractive index gradient transition layer (50nm), a structural adhesive layer (30μm), and a hydrophobic and oleophobic coating (30nm). The structural adhesive layer is an interpenetrating copolymer network formed by curing linear acrylate copolymer and HPUA at a weight ratio of 70:12; The refractive index difference between the substrate layer and the refractive index gradient transition layer is 0.008, and the refractive index difference between the refractive index gradient transition layer and the structural adhesive layer is 0.008. Both the refractive index gradient transition layer and the structural adhesive layer consist of nano-zirconia modified with silane coupling agent KH-560, and the Dv of the nano-zirconia modified with silane coupling agent... 50 =8nm.
[0099] 2. The method for preparing the hydrogel membrane provided in this embodiment includes: (1) Preparation of optical substrate layer: TPU film with a thickness of 100μm (transmittance > 93%, haze < 1%), and corona treatment of TPU film to make its surface tension reach 52dyn / cm.
[0100] (2) Coating and curing of the refractive index gradient transition layer: a. A nano-zirconia dispersion with a solid content of 30wt% modified by silane coupling agent was mixed with isooctyl acrylate (IOA) in different proportions and pre-dispersed for 30 minutes in a high-speed disperser at a speed of 1500 rpm to obtain five primary dispersions of different concentrations (5wt%, 10wt%, 15wt%, 20wt%, and 25wt%). b. Transfer the primary dispersion to a three-roll mill or a bead mill for fine grinding for 1.5 hours to obtain a uniform and stable refractive index gradient transition layer slurry.
[0101] Process: On one side of the treated TPU film, a 5wt% concentration slurry is applied using a micro-grooved roller coater, with the wet film thickness controlled at 34nm. Pre-curing is performed by irradiating with a UV-LED lamp for 2 seconds. Immediately after the pre-cured coating, a 10wt% concentration slurry is applied, with the wet film thickness controlled at 34nm, and pre-cured for 2 seconds. This process is repeated, successively applying 15wt%, 20wt%, and 25wt% concentration slurries, maintaining consistent wet film thickness and pre-curing time for each layer. After five layers are applied, final curing is performed using a UV lamp to form a refractive index gradient transition layer with a total dry film thickness of 50nm.
[0102] (3) Preparation of structural adhesive layer grout: The raw materials and pretreatment are shown in Table 1 below: Table 1
[0103] Equipment: Planetary mixer.
[0104] step: ① Preparation of the main premix: Add the pretreated component A to the stirred tank, start stirring, and set the speed to 200 RPM. Slowly add 8 parts of D1 and stir for 5 minutes until uniform. Then add 1.5 parts of E1 and 0.5 parts of E3 in sequence, and continue stirring at 200 RPM for 10 minutes until completely dissolved and dispersed to obtain a uniform and transparent premix.
[0105] ② Introduce component B: Slowly add the preheated HPUA (80g / min) to the above premixed liquid, increase the stirring speed to 400rpm, and observe the material in the vessel after stirring for 20 minutes. It should become a uniform, viscous, transparent liquid with no visible particles or phase separation.
[0106] ③ Introduce component C and remaining additives: While stirring at 400 rpm, slowly add 20 parts of component C in a thin stream (110 g / min), followed by 1 part of D2, and finally 1 part of E2. Increase the speed to 600 rpm and continue stirring for 25 minutes to ensure that the nanoparticles are fully dispersed and the system is homogeneous.
[0107] ④ Degassing and Filtration: Stop stirring, seal the mixing vessel, and turn on the vacuum system to degas for 30 minutes until the liquid surface is calm and no bubbles escape. Filter the degassed slurry through a 10μm pore size nylon filter bag under pressure, and collect the filtrate to obtain the final structural adhesive slurry.
[0108] (4) Coating and curing of structural adhesive layer: The prepared structural adhesive slurry is injected into the coating machine trough and coated on the film surface with a refractive index gradient transition layer. The wet film thickness is controlled at 60μm. After coating, the film material is placed in a nitrogen-protected UV curing chamber for segmented curing. The first stage of pre-curing is UV-LED (wavelength of 395nm, power of 200mW / cm). 2 Irradiation for 3 seconds causes rapid surface gelation. The second stage of deep curing is achieved using UV-LED (wavelength 365nm, power 1000mW / cm²). 2 Irradiate for 60 seconds to ensure the adhesive layer is fully cured and forms an IPN structure.
[0109] (5) Coating a hydrophobic and oleophobic coating: Using a fluorosilane (perfluorooctyltriethoxysilane) solution, spray coating is applied to the other side of the TPU film, and heat treatment is carried out in an oven at 120°C for 30 min to form a 30 nm hydrophobic and oleophobic coating.
[0110] (6) Curing and cutting: The prepared composite film roll is placed in a constant temperature and humidity environment of 23℃ and 50%RH for 48 hours to complete the curing process, and then cut into finished hydrogel film according to the product size.
[0111] Example 2 1. The difference between the hydrogel membrane provided in this embodiment and that in embodiment 1 is that the thickness of the refractive index gradient transition layer is 100 nm.
[0112] 2. The difference between the preparation method of the hydrogel membrane provided in this embodiment and that in embodiment 1 is that: in step (2), the wet film thickness of each layer of slurry is adjusted from 34nm in embodiment 1 to 68nm in the coating process.
[0113] Example 3 1. The difference between the hydrogel membrane provided in this embodiment and that in embodiment 1 is that the thickness of the refractive index gradient transition layer is 200 nm.
[0114] 2. The difference between the preparation method of the hydrogel membrane provided in this embodiment and that in embodiment 1 is that: in step (2), the wet film thickness of each layer of slurry is adjusted from 34nm in embodiment 1 to 136nm in the coating process.
[0115] Example 4 1. The difference between the hydrogel membrane provided in this embodiment and that in Example 1 is that the nano-zirconia modified with a silane coupling agent has a Dv... 50 =15nm.
[0116] 2. The difference between the preparation method of the hydrogel membrane provided in this embodiment and that in Example 1 is that the nano-zirconia modified with a silane coupling agent has a Dv 50 =15nm, its preparation method is the same as that of the nano-zirconia dispersion modified with silane coupling agent with a solid content of 30wt% in Example 1 (particle size Dv) 50 Difference in preparation method between 8nm and 8nm: When Dv50 is stable at 15nm and the particle size distribution shows a narrow single-peak distribution, grinding is stopped.
[0117] Example 5 1. The difference between the hydrogel membrane provided in this embodiment and that in embodiment 1 is that there is no refractive index gradient transition layer, and the refractive index difference between the substrate layer and the structural adhesive layer is 0.005.
[0118] 2. The difference between the preparation method of the hydrogel membrane provided in this embodiment and that in Example 1 is that the solid content is 30wt% and it is a nano-zirconia dispersion modified with a silane coupling agent (particle size Dv). 50 18 parts (8nm) (equivalent to 5.4 parts of nano-zirconia modified with silane coupling agent).
[0119] Example 6 1. The difference between the hydrogel membrane provided in this embodiment and that in embodiment 1 is that there is no refractive index gradient transition layer, and the refractive index difference between the substrate layer and the structural adhesive layer is 0.016.
[0120] 2. The difference between the preparation method of the hydrogel membrane provided in this embodiment and that in embodiment 1 is that no refractive index gradient transition layer is coated and cured.
[0121] Example 7 1. The difference between the hydrogel membrane provided in this embodiment and that in embodiment 1 is that the thickness of the refractive index gradient transition layer is 350 nm.
[0122] 2. The difference between the preparation method of the hydrogel membrane provided in this embodiment and that in embodiment 1 is that: in step (2), the wet film thickness of each layer of slurry is increased from 34nm in embodiment 1 to 238nm in the coating process.
[0123] Example 8 1. The difference between the hydrogel membrane provided in this embodiment and that in Example 1 is that the nano-zirconia modified with a silane coupling agent has a Dv... 50 =20nm.
[0124] 2. The difference between the preparation method of the hydrogel membrane provided in this embodiment and that in Example 1 is that the nano-zirconia modified with a silane coupling agent has a Dv 50 =20nm, its preparation method is the same as that of the nano-zirconia dispersion modified with silane coupling agent with a solid content of 30wt% in Example 1 (particle size Dv) 50 The difference in preparation methods for 8nm is as follows: When Dv50 is stable at 20nm and the particle size distribution shows a narrow single-peak distribution, grinding is stopped.
[0125] Example 9 1. The difference between the hydrogel membrane provided in this embodiment and that in Example 1 is that HPUA is replaced with HBP-EA (hyperbranched polyether acrylate, purchased from Perstorp, Sweden, Boltorn® H2004), and HBP-EA has 16 end polymerizable functional groups.
[0126] 2. The difference between the preparation method of the hydrogel membrane provided in this comparative example and that in Example 1 is that in step (3), HPUA is replaced with HBP-E-A.
[0127] Example 10 1. The difference between the hydrogel membrane provided in this embodiment and that in Example 1 is that HPUA is replaced with HBP-AM-A (hyperbranched polyamide derivative, purchased from DSM in the Netherlands, Hybrane® H1500), and the number of end polymerizable functional groups of HBP-AM-A is 8.
[0128] 2. The difference between the preparation method of the hydrogel membrane provided in this comparative example and that in Example 1 is that in step (3), HPUA is replaced with HBP-AM-A.
[0129] Example 11 1. The difference between the hydrogel membrane provided in this comparative example and Example 1 is that HPUA is replaced with PET4A (a star-shaped oligomer of pentaerythritol tetraacrylate, purchased from Sartoma Company SR295), and the number of end polymerizable functional groups of PET4A is 4.
[0130] 2. The difference between the preparation method of the hydrogel membrane provided in this comparative example and that in Example 1 is that in step (3), HPUA is replaced with PET4A.
[0131] Comparative Example 1 1. The difference between the hydrogel membrane provided in this comparative example and that in Example 1 is that it does not contain HPUA.
[0132] 2. The difference between the preparation method of the hydrogel membrane provided in this comparative example and that in Example 1 is that HPUA is not introduced in step (3).
[0133] Comparative Example 2 1. The difference between the hydrogel membrane provided in this comparative example and Example 1 is that HPUA is replaced with linear polyurethane acrylate (PUA, purchased from Allnex EBECRYL® 8402, which has 2 end polymerizable functional groups), and the copolymer with linear acrylate forms the traditional IPN structure.
[0134] 2. The difference between the preparation method of the hydrogel membrane provided in this comparative example and that in Example 1 is that in step (3), HPUA is replaced with PUA.
[0135] Comparative Example 3 1. The difference between the hydrogel membrane provided in this comparative example and that in Example 1 is that the linear acrylate copolymer is replaced with a branched acrylate copolymer (CN9011 purchased from Sartomer Arkem), and the branched acrylate copolymer has 6 end polymerizable functional groups.
[0136] 2. The difference between the preparation method of the hydrogel membrane provided in this comparative example and that in Example 1 is that the linear acrylate copolymer in step (3) is replaced with a branched acrylate copolymer.
[0137] Test case (1) 180° peel force: Refer to national standard GB / T 2792-2014.
[0138] (2) Total light transmittance: Refer to national standard GB / T-2410-2008.
[0139] (3) Haze: Refer to the national standard GB / T-2410-2008.
[0140] (4) Indentation self-healing time: A fixed load (50g) was applied to the surface of the hydrogel film adhesive layer using a microhardness tester and held for 10 seconds to form an indentation. The load was then removed, and the sample was placed in an environment of 25°C and 50%RH. The morphology of the indentation was observed using an optical microscope or a laser confocal microscope, and the time required from the removal of the load to the complete disappearance of the indentation was recorded.
[0141] (5) Edge lifting after bonding to curved surfaces: Cut the hydrogel film sample into 100mm × 25mm pieces and attach it tightly to a glass rod with a specified radius of curvature R=5mm, ensuring no initial air bubbles. Place it under specified high temperature and high humidity conditions (60℃, 90%RH) for 72 hours. After removal, visually observe the edge of the film under a standard light source to see if warping, bubbling, or edge lifting occurs, and evaluate it according to the following levels: Level 0 (no warping), Level 1 (slight edge warping, length <5%), Level 2 (obvious warping, length 5%~20%), Level 3 (severe warping, length >20%).
[0142] The performance test results of the hydrogel membranes provided in the above embodiments and comparative examples are shown in Table 2 below.
[0143] In Table 2, the variables refer to those compared to Example 1.
[0144] Table 2 Performance test data of the examples and comparative examples
[0145] As shown in Table 2: In Comparative Example 1, without hyperbranched HPUA, the peel strength plummeted to 480 gf, and the indentation self-healing time proved that the high adhesion of the hydrogel film is closely related to the dense polar anchoring points provided by the HPUA spherical structure.
[0146] Comparative Example 2 replaced the hyperbranched polymer and / or star polymer with PUA, forming a traditional IPN structure. Since the polymers only interweave and penetrate each other at the molecular level without mutual covalent bonds, they cannot form a stable network with both high crosslinking density and excellent interpenetrating structure as in this invention. As a result, the peel adhesion and pressure self-healing ability are significantly degraded.
[0147] The linear polymer in Comparative Example 3 was replaced with a branched acrylate copolymer, forming a rigid and difficult-to-extend branched crosslinked backbone. This is not conducive to the interpenetration of the second polymer during the curing process and the embedding of the subsequent second polymer as a crosslinking node. It also cannot form a stable network with high crosslinking density and excellent interpenetrating structure as in this invention. The peel adhesion and pressure self-healing ability are significantly degraded.
[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A hydrogel membrane, characterized in that, Includes a substrate layer and a structural adhesive layer; The structural adhesive layer includes an interpenetrating copolymer network, which includes an interpenetrating first three-dimensional cross-linked network and a second three-dimensional cross-linked network. The first three-dimensional cross-linked network is formed by intermolecular cross-linking and curing of a first polymer, and the second three-dimensional cross-linked network is formed by intermolecular cross-linking and curing of a second polymer. The first polymer comprises a linear polymer, the linear polymer comprising a first polymerizable functional group; The second polymer includes hyperbranched polymers and / or star polymers, wherein the ends of the hyperbranched polymers and / or star polymers include second polymerizable functional groups complementary to the first polymerizable functional group; The first three-dimensional cross-linked network and the second three-dimensional cross-linked network are connected by covalent bonds through the interaction of the first polymerizable functional group and the second polymerizable functional group.
2. The hydrogel membrane according to claim 1, characterized in that, The mass ratio of the first polymer to the second polymer is (40~70):(8~24).
3. The hydrogel membrane according to claim 1, characterized in that, The number of the second polymerizable functional groups is ≥16; the second polymerizable functional group is selected from at least one of acrylate group, vinyl ether group, and allyl ether group, preferably acrylate group; Preferably, the hyperbranched polymer is selected from at least one of hyperbranched polyester, hyperbranched polyether, and hyperbranched polyamide; the star-shaped polymer is selected from at least one of star-shaped polyacrylate and star-shaped polystyrene. More preferably, the second polymer is selected from hyperbranched polyurethane acrylate.
4. The hydrogel membrane according to claim 1, characterized in that, The linear polymer is a linear acrylate polymer; Preferably, the linear acrylate polymer is selected from homopolymers of one of isooctyl acrylate, isobornyl acrylate, and hydroxyethyl acrylate, or copolymers of at least two of them. More preferably, the linear polymer is selected from acrylate copolymers.
5. The hydrogel membrane according to claim 1, characterized in that, The thickness of the structural adhesive layer is ≥25μm, preferably 25~50μm.
6. The hydrogel membrane according to claim 1, characterized in that, The refractive index difference between the substrate layer and the structural adhesive layer is ≤0.
01.
7. The hydrogel membrane according to claim 1, characterized in that, The hydrogel membrane further includes a refractive index gradient transition layer, which is located between the substrate layer and the structural adhesive layer. The refractive index of the substrate layer is denoted as n1; The refractive index of the refractive index gradient transition layer is denoted as n2; The refractive index of the structural adhesive layer is denoted as n3; The n1, n2, and n3 satisfy the following condition: n1 < n2 < n3; Preferably, the thickness of the refractive index gradient transition layer is 50~200nm.
8. The hydrogel membrane according to claim 7, characterized in that, The structural adhesive layer comprises a refractive index modifier modified with a silane coupling agent; and / or, the refractive index gradient transition layer comprises a refractive index modifier modified with a silane coupling agent. The refractive index modifier without silane coupling agent modification is selected from at least one of nano-sized ZrO2, TiO2, Ta2O5, Nb2O5, and HfO2, preferably nano-sized ZrO2; Preferably, the refractive index modifier modified with silane coupling agent has a Dv50 ≤ 15 nm.
9. A method for preparing the hydrogel membrane according to any one of claims 1 to 8, characterized in that, include: The hydrogel film is prepared by depositing a structural adhesive slurry comprising the first polymer and the second polymer onto the substrate layer and then curing it. Preferably, the curing reaction includes: a pre-curing reaction that enables the hyperbranched polymer or star polymer to achieve a conversion rate of 60% to 70%; The photocuring wavelength of the pre-curing reaction is 365nm~405nm, and the photocuring power is 100mW / cm². 2 ~500mW / cm 2 .
10. The application of the hydrogel membrane according to any one of claims 1 to 8 in the protection of electronic devices; Preferably, the electronic device includes a display cover glass, an optical lens module, a flexible display module, a touch sensor, a biometric sensor cover, or an in-vehicle display panel.